Reduction of BMPR2 mRNA expression in peripheral blood of pulmonary arterial hypertension patients: A marker for disease severity? - Theobald, Vivienne; Benjamin, Nicola; Seyfarth, Hans-Jürgen; Halank, Michael; Schneider, Marc; Richtmann, Sarah; Hinderhofer, Katrin; Xanthouli, Panagiota; Egenlauf, Benjamin; Seeger, Rebekka; Hoeper, Marius M.; Jonigk, Danny; et al. (Genes, 2022)
Pulmonary arterial hypertension (PAH) can be caused by pathogenic variants in the gene bone morphogenetic protein receptor 2 (BMPR2). While BMPR2 protein expression levels are known to be reduced in the lung tissue of heritable PAH (HPAH) patients, a systematic study evaluating expression in more easily accessible blood samples and its clinical relevance is lacking. Thus, we analyzed the BMPR2 mRNA expression in idiopathic/HPAH patients and healthy controls in blood by quantitative polymerase chain reaction and protein expression by enzyme-linked immunosorbent assay. Clinical parameters included right heart catherization, echocardiography, six-minute walking test and laboratory tests. BMPR2 variant-carriers (n = 23) showed significantly lower BMPR2 mRNA expression in comparison to non-carriers (n = 56) and healthy controls (n = 30; p < 0.0001). No difference in BMPR2 protein expression was detected. Lower BMPR2 mRNA expression correlated significantly with greater systolic pulmonary artery pressure and pulmonary vascular resistance. Higher BMPR2 mRNA expression correlated with greater glomerular filtration rate, cardiac index and six-minute walking distance. We demonstrated the feasibility to assess BMPR2 expression in blood and, for the first time, that BMPR2 mRNA expression levels are significantly reduced in variant carriers and correlated with clinical parameters. Further studies may evaluate the usefulness of BMPR2 mRNA expression in blood as a new marker for disease severity.